Metal oxide/chitosan composite for organic pollutants removal: A comprehensive review with bibliometric analysis - Khairunnas Ahmad; Williams Chiari (Narra X, 2023)
Organic pollutants are now a global concern because of their rapid increase following the rapid industrial growth. In tackling this problem, researchers have used chitosan that could act as adsorbing material. However, chitosan use in wastewater treatment requires further modification owing to its drawbacks of being susceptible to acidic environment and mechanically weak. Of many modifying approaches, metal-oxide embedment is perceived as promising because not only does it improve the chemical and physical properties of chitosan, but it also adds new features to the material such as being magnetic or photocatalytic. This present review describes the modification of chitosan through metal oxide embedment aiming to its utility in organic waste removal. Firstly, the definition of chitosan and the progress of its application in wastewater treatment are presented. Types of metal oxides, namely photocatalyst and magnetic iron oxide are also discussed. Embedment of metal oxides into chitosan could be done using methods such as sol-gel, high-energy ball milling, and spray-drying, where they affect the chemical and physical properties of the produced metal oxide/chitosan composites. Reported studies suggest a high percentage of organic pollutant removal, up to 100%. In addition to its removal ability, metal oxide/chitosan is also proven to be environmentally friendly and economical.